Isolation of Lacustrine Basins and Marine Regression in the Kuujjuaq Area, Northern Québec, as Inferred from Diatom Analysis - Pienitz, Reinhard; Lortie, Guy; Allard, Michel (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1991)
ABSTRACTThe Holocene sediment records of two lakes, located 50 km south of the Ungava Bay coast near Kuujjuaq have been examined using diatom analysis in order to trace basin isolation from marine influence. The succession of diatom zones clearly documents paleoenvironmental changes induced by glacio-isostatic uplift and regression of postglacial D'lberville Sea through consecutive periods of marine occupation, isolation from the sea and subsequent lacustrine conditions. Diatom analysis proved to be an effective tool in identifying the position of the isolation contact in the sediment columns and in defining the related changes in paleosalinity and isolation dynamics. Based on the Sedated isolation contacts and the threshold elevations of both lakes, a tentative emergence curve has been reconstructed which is in agreement with curves from adjacent areas. This allowed, for the first time, to infer trends in glacio-isostatic rebound and duration of marine submergence for an area from which paleogeographical data are almost entirely lacking. The curve shows that, following déglaciation about 7000 years ago, the Kuujjuaq area experienced continuous and rapid emergence in the order of 5.7-5.8 m/century until 4800-4300 years BP. Thereafter, emergence slowed to a rate of approximately 0.9 m/century. This study provides further evidence for the usefulness of diatom analysis in reconstructing sea-level changes and land uplift of formerly glaciated regions.